2019
DOI: 10.1042/cs20190394
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA-104718 acts as competing endogenous RNA and promotes hepatocellular carcinoma progression through microRNA-218-5p/TXNDC5 signaling pathway

Abstract: Accumulating evidences indicate that circular RNAs (circRNAs) play a vital role in diverse cancer biology. However, the contributions of circRNAs to hepatocellular carcinoma (HCC) and their underlying mechanism remain largely unknown. The present study aims at investigating the role of circRNA-104718 in HCC progression, which has been observed to be significantly up-regulated in HCC tissues. We found that, higher expression of circRNA-104718 also leds to a poor prognosis in HCC patients. Using luciferase bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 41 publications
5
76
0
Order By: Relevance
“…Concerning the specific function of circMAST1 in cell proliferation, we found that cyclin A, cyclin E, CDK1, and CDK2 expression levels were changed owing to circMAST1 silencing Our data also showed that circMAST1 silencing inhibited HCC cell migration and invasion, which are important determinants of tumor metastasis 35 . These results are consistent with those of previous studies that showed a regulatory role for circRNAs in cancer migration and invasion [36][37][38][39][40] .…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the specific function of circMAST1 in cell proliferation, we found that cyclin A, cyclin E, CDK1, and CDK2 expression levels were changed owing to circMAST1 silencing Our data also showed that circMAST1 silencing inhibited HCC cell migration and invasion, which are important determinants of tumor metastasis 35 . These results are consistent with those of previous studies that showed a regulatory role for circRNAs in cancer migration and invasion [36][37][38][39][40] .…”
Section: Discussionsupporting
confidence: 93%
“…Growing evidence indicates that the deregulation of miRNAs occurs in HCC progression 29 and recent studies have further developed the miRNA-based risk of HCC recurrence following liver resection. 30 Results of miRNA therapies in HCC showed that either reintroducing suppressor miRNAs or inhibiting oncogenic miRNAs suppress HCC progression in various HCC cell lines in vitro, animal models in vivo, and human clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that circRNAs are mainly produced by RNA cleavage, are widely present throughout eukaryotic cells, and have high stability, species conservation, and tissue specificity. CircRNAs are also involved in intracellular RNA regulation networks and are closely associated with the development of many diseases, including systemic sclerosis and several cancer types, such as liver, lung, stomach, oral, nasopharyngeal, ovarian, prostate, uterine, kidney, and bladder cancers (Liu H. et al, 2019;Wang et al, 2019;Wu et al, 2019;Yao et al, 2019;Yu et al, 2019;Zhang et al, 2019;Zhi et al, 2019). Moreover, it has been reported that circRNAs act as RNA sponges, binding to their corresponding miRNAs to regulate the expression of target genes (Memczak et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that circRNAs are stable, specific, and abundant (Wang et al, 2018;Yu et al, 2019;Zhi et al, 2019), making them suitable for detection as circulating biomarkers in liquid biopsies. Indeed, we identified some differentially expressed circRNAs in PCC/PGL patients, such as hsa_circ_0000567, hsa_circ_0002897, and hsa_circ_0004473, that bind to miRNA and affect histone methylation; these three circRNAs were also found differentially expressed between the peripheral blood of PCC/PGL patients and healthy donors.…”
Section: Discussionmentioning
confidence: 99%